Método para la determinación del valor económico del servicio ambiental del área verde del valle de Moche - Montoya Colmenares, Patricia Clementina (2020)
ABSTRACT The conservation of the fragile urban valleys in the cities of Peru, especially in the coastal cities, is a claim of common sense that acquires more and more relevance in the public debate. Thinking about the sustainability of cities means assuming the conservation of the scarce natural and cultural resources that sustain them, many of which are an essential part of their valleys. For this we need innovative economic instruments that encourage the conservation of natural resources. In this framework it is that we consider as objective in the present investigation work, to identify the method to determine the economic value of the environmental service of the green area of the Moche Valley. For the identification of the method the inductive-deductive methodology was used, as well as the survey was applied in the Moche Valley to obtain the data with which the economic value that people give to the environmental service of In this valley, valuable information was also obtained regarding the fact that in their entirety the respondents agree on the need to conserve the valley and a high percentage believe that the displacement of agricultural lands through urban areas should be stopped, as well as the provision to pay to conserve the green area of the Moche valley. Through the aforementioned method, the economic value of the green area of the Moche Valley was determined, as well as the main variables that influence the willingness to pay, such as: family income, education level, information, needs of housing of the population, economic activity of the respondent.